2010
DOI: 10.4081/ija.2010.233
|View full text |Cite
|
Sign up to set email alerts
|

Habitat improvements with wildlife purposes in a grazed area on the Apennine Mountains

Abstract: In many European countries, the abandonment of traditional practices in the last decades produced remarkable effects on agricultural land use. In marginal mountain lands, one of the most evident outcomes is the reduction of the surfaces occupied by open habitats, mostly represented by meadows and pastures. The ecological consequences of reduced grazing in the pastures concerned not only the vegetation structure but also the floristic composition and the biodiversity of the herbaceous component, which is modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Wild animals in our trial showed performances similar to what described by Orth et al (1998), by Moser et al (2008) or by Freschi et al (2014), concerning variability of animal utilisation according to seasonal changes in food resources availability, or by Boulanger et al (2015) that reported high browsing activity performed by wild ungulates on species of no quality or even toxic. Concerning level of utilisation, data of percentage of browsing is consistent with those of Ponzetta et al (2010) and Iussig et al (2015).…”
Section: Articlesupporting
confidence: 78%
See 2 more Smart Citations
“…Wild animals in our trial showed performances similar to what described by Orth et al (1998), by Moser et al (2008) or by Freschi et al (2014), concerning variability of animal utilisation according to seasonal changes in food resources availability, or by Boulanger et al (2015) that reported high browsing activity performed by wild ungulates on species of no quality or even toxic. Concerning level of utilisation, data of percentage of browsing is consistent with those of Ponzetta et al (2010) and Iussig et al (2015).…”
Section: Articlesupporting
confidence: 78%
“…Thus we can say that animal selection is narrowly related to the vegetation context in which a species grows (Orth et al, 1998). The reduced importance of pastoral value to explain wild animals browsing in forage resources was already pointed out by Ponzetta et al (2010) and it is mainly due to specific indexes that are generally studied for domestic stocks. For these reasons, it was suggested to propose a list of specific indexes especially focused on wild animal intake to have a proper assessment of pastoral value for faunistic purposes .…”
Section: Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most evident consequences due to abandonment is the contraction of the surface occupied by open habitats (Orlandi et al 2016), especially grasslands and pastures, in marginal territories that are re-colonised by shrubs and trees (Grau et al 2019). This is because many of these areas are mainly semi-natural resources and were created in the past to provide forage available to grazing animals (Feurdean et al 2018), their conservation is thus deeply linked to a proper management (Ponzetta et al 2010; Kulik et al 2020). The progressive afforestation causes as a consequence the reduction of biodiversity in these environments, particularly with respect to some plant species (Valkó et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of sustainable grazing systems, aiming at the mitigation of negative impacts deriving from excessive or reduced grazing, such as biodiversity loss [1], requires specific knowledge of plant ecophysiology associated with herbivore grazing behaviour and dynamics [2]. Thus, understanding the drivers of resource selection and mechanisms adopted by animals in order to cope with environmental conditions is crucial in free-ranging systems [3].…”
Section: Introductionmentioning
confidence: 99%